Psychosocial interventions for the prevention of self-harm repetition: protocol for a systematic review and network meta-analysis - Andrea Cipriani; Jill Boruff; Samuele Cortese; Cinzia Del Giovane; Massimiliano Orri; Toshiaki A Furukawa; Dennis Ougrin; Marie-Claude Geoffroy; Gustavo Turecki; Anthony J Gifuni; Dalia Schaffer; Ayla Inja (BMJ Open, 2023)
Introduction Suicide is an important public health problem. Providing evidence-based psychosocial interventions to individuals presenting with self-harm is recognised as an important suicide prevention strategy. Therefore, it is crucial to understand which intervention is most effective in preventing self-harm repetition. We will evaluate the comparative efficacy of psychosocial interventions for the prevention of self-harm in adults.Methods and analysis We will perform a systematic review and network meta-analysis (NMA) of randomised controlled trials (RCTs) testing psychosocial interventions for the prevention of self-harm repetition. We will include RCTs in adults (mean age: 18 years or more) who presented with self-harm in the 6 months preceding enrolment in the trial. Interventions will be categorised according to their similarities and underpinning theoretical approaches (eg, cognitive behavioural therapy, case management). A health sciences librarian will update and adapt the search strategy from the most recent Cochrane pairwise systematic review on this topic. The searches will be performed in MEDLINE (Ovid), Embase (Ovid), PsycInfo (Ovid), CINAHL (EBSCO), Cochrane Central (Wiley), Cochrane Protocols (Wiley), LILACS and PSYNDEX from 1 July 2020 (Cochrane review last search date) to 1 September 2023. The primary efficacy outcome will be self-harm repetition. Secondary outcomes will include suicide mortality, suicidal ideation and depressive symptoms. Retention in treatment (ie, drop-outs rates) will be analysed as the main acceptability outcome. Two reviewers will independently assess the study eligibility and risk of bias (using RoB-2). An NMA will be performed to synthesise all direct and indirect comparisons. Ranked forest plots and Vitruvian plots will be used to represent graphically the results of the NMA. Credibility of network estimates will be evaluated using Confidence in NMA (CINeMA).Ethics and dissemination As this is the protocol for an aggregate-data level NMA, ethical approval will not be required. Results will be disseminated at national/international conferences and in peer-review journals.Trial registration number CRD42021273057.